Piano Works by Dora Pejačević – A Personal Perspective of an Interpreter - Kyra Steckeweh (Arti Musices)
This article illuminates the significance and impact of Dora Pejačević’s piano compositions through the lens of a performing artist. Dora Pejačević (1885–1923), a Croatian noblewoman and composer, emerges as a figure of profound musical depth and innovation. The article begins with an evocative description of Pejačević improvising at the piano, a scene recounted by Countess Sidonie Nádherný von Borutin in a letter to the poet Rainer Maria Rilke dated 5 October 1914. This anecdote serves as a poignant entry point into Pejačević’s world. Central to the article is the exploration of Pejačević’s Piano Sonata, Op. 36, composed during the First World War. The interpretative perspective sheds light on the nuanced relationship between Pejačević’s compositional process and her personal experiences. The author argues that Pejačević’s music is not merely a reflection of her inner world but also a response to the external realities she faced. This dual focus highlights Pejačević’s ability to channel her emotional and intellectual energies into a musical language that is both deeply personal and universally resonant. The discussion extends to the broader context of Pejačević’s piano compositions, which are categorized into three distinct phases: early works reflecting her Romantic and Classical influences, middle-period compositions showing a mature late-Romantic style, and late works characterized by far-reaching harmonies and formal freedom, marking a stylistic turning point in her oeuvre. The article highlights Pejačević’s precision in musical notation and her ability to clearly communicate her musical ideas. Moreover, the article underscores the significance of Pejačević’s piano works within her broader musical oeuvre, noting that these compositions represent the largest body of her work and showcase her evolution as a composer. Through an examination of specific pieces, the author illustrates Pejačević’s stylistic development.